Typhoid intestinal perforation: Point-of-care ultrasound as a diagnostic tool in a rural Ugandan Hospital - Chanler-Berat, Jordan; Birungi, Alfunsi; Dreifuss, Brad; Mbiine, Ronald (African Journal of Emergency Medicine, 2016)
The utility of point-of-care ultrasound (POCUS) in austere environments has been demonstrated in the literature. Particularly in settings where advanced imaging is either lacking or extraordinarily difficult and costly to obtain, ultrasound can help providers rapidly screen and diagnose patients. We report a case in which a non-physician trained in POCUS was able to detect bowel perforation with ultrasound. We believe this demonstrates the potential utility of teaching bedside ultrasound to all providers in resource-limited Emergency Centres (ECs).
Keywords: Typhoid intestinal perforation; Ultrasound; Rural Ugandan Hospital